الجيش ودوره في توطيد أركان دولة بني أمية في الأندلس (Journal of Humanitarian and Applied Sciences, 2023)
Since its inception, the Islamic State has relied on the military establishment, where it played a role in the Islamic conquests of Andalusia and was characterized by its organization and its ability to keep up with what is emerging through its continuous development, modernization and funding with enough funds. This study talks about the role of the military in consolidating the rule of the Umayyads in Andalusia by Abdel Rahman Al-Dakhil, who was interested in developing the army and eliminating the problems it faced, a policy that his successors followed after him.